التماثل والاختلاف في المعتقد المذهبي للوالدين وأثره في تنمية الاتجاه التعصبي المذهبي لابنائهم (Journal Of Educational and Psychological Researches, 2013)
This study aims at measuring the sectarian prejudice attitude with sample of college student and secondary school students. It also aims at detecting the impact of similarities and differences of the sectarian belief with the parents on the development of sectarian prejudice with their parents according the following variables (gender,grade,achievement of the parents). The study restricted by a sample consists of (Baghdad,Al-mustansiriya,and Al-Qadisiyah) students and the fourth grade students (males and female). To achieve the goal of this study , the researcher built atoll to measure the sectarian prejudice attitude after verifying its psychometric characteristics , after analyzing the data by applying (t-test) of two independent samples and (one way anova), the researcher reaches on that the number of the students with low level of prejudice is less who with low level of prejudice , and the mean of the students who their parents from the same sect is less than the students who their parents from different sect . also there are differences in sectarian prejudice attitude between the students of the university of Baghdad and the students of Al-Qadisiyah for the university of Al-Qadisiyah. The study reveals differences in sectarian prejudice attitude due to the achievements of parents for the low levels of  achievements, where there are no differences due to sex variable.